If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 3 = 3x + 20 Reorder the terms: 3 + 2x = 3x + 20 Reorder the terms: 3 + 2x = 20 + 3x Solving 3 + 2x = 20 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 3 + 2x + -3x = 20 + 3x + -3x Combine like terms: 2x + -3x = -1x 3 + -1x = 20 + 3x + -3x Combine like terms: 3x + -3x = 0 3 + -1x = 20 + 0 3 + -1x = 20 Add '-3' to each side of the equation. 3 + -3 + -1x = 20 + -3 Combine like terms: 3 + -3 = 0 0 + -1x = 20 + -3 -1x = 20 + -3 Combine like terms: 20 + -3 = 17 -1x = 17 Divide each side by '-1'. x = -17 Simplifying x = -17
| 7x+2(x-5)=4 | | 5X+6+4X=3-6 | | 10(x+2)-4(2x+1)=2(x+6) | | E^9x=5.9 | | F(x)=-x^2+8x+7 | | 9n+2n-5=-60 | | 8(a+2)=72 | | F(x)=-x^2-6x+5 | | 3x-4+5x+20=180 | | 3x-4+5x+20=360 | | 5=log(x+1) | | 8+5(x-7)=8-4(x-8) | | 5X-7X+X=4-2X | | 5e+2.5=2.5-7.5c | | -5.5+3.5(1-9.5k)=25.5 | | 0.24x+3.8x=-2.02 | | 8+5x-35x=8-4x-32 | | 4(2b-3x)=7b+5x | | 8+5x-35x=8-4x+32 | | 8x-17b=7x | | n=2/4*7/8 | | 7+3x=-5x+13 | | 12x-(x+3)=30 | | 4(2x-3b)=7x+5b | | 12x-(x+3)=4 | | 2x-3+4x+1=0 | | l-100=253 | | 9y-9=6y+6 | | 18x^2+3-53x=0 | | -3z+8=-12+2z | | 4y=70+5x | | h=7*6/7 |